Aprender a palavra ao ar livre : estratégias de modernidade sanitária em Portugal no início do séc. XX - Amaral, Anabela (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
Taking as its starting point the disease that frightened society by being unknown to its cure, the medical profession was called to intervene in order to design conservation strategies of social future. The school and the teachers, as child trainers strive towards reconciling a dual function, teaching and to preserve their health. Hygienists speeches and medical discussions analyzed the illness, the committed relationship with the future and with the healthy child, combining the scientific and pedagogical issues. Teaching strategies are designed to preserve the life of the student and the teacher, including school outdoors. The apology for outdoor living, strongly inspired by the sanatorium model, and the treatment and prophylaxis of tuberculosis, conditioned and influenced the pedagogical routines with new devices and school conceptions.